On hysteresis in a variable pitch fan transitioning to reverse thrust mode and back - Vitlaris, Dimitrios; Rajendran, David John; Tunstall, Richard; Whurr, John; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2025)
A novel hysteresis phenomenon during the transition to and back from the reverse thrust mode in a variable pitch fan (VPF) is identified and characterized in this work. This is done using a three-dimensional fully transient unsteady Reynolds-averaged Navier–Stokes (URANS) with the transitioning fan blade airfoils simulated by an adaptation of the mesh displacement method. A “real-time” simulation of the complete VPF hysteresis loop is achieved by specifying a blade wall motion through an Eulerian rotation matrix in differential, gradual steps, and is combined with a mesh probe-and-update routine for improved numerical accuracy and stability. The VPF is modeled to be transitioning in a modern 40000 lbf geared high bypass ratio turbofan engine architecture at “Approach Idle” engine power setting in a typical twin-engine airframe with the flaps, slats, and spoilers set for an aircraft touchdown airspeed of 140 knots. The transition to reverse thrust mode involves flow starvation into the engine, formation of recirculation zones in the bypass duct and the establishment of the reverse stream, all of which occurs in the opposing presence of the freestream flow at aircraft touchdown velocity. The transition back to forward flow mode involves the gradual reestablishment of the freestream, which is opposed by the presence of the reverse stream within the engine. It is quantified that in the transition to reverse thrust, the blockage develops with a larger time delay than the disappearance of the blockage during the transition back due to the interplay of the temporal dynamics of fan blade motion and flow field response. The details of the changes in the flow field behavior, the effect of engine power setting and aircraft touch-down velocity on the hysteresis behavior are explained in detail in the paper. Additional manifestations of the hysteresis phenomena at reverse thrust involving engine spool-up and down, and aircraft acceleration-deceleration maneuvers are also explored. The hysteresis phenomena described in this work are critical in properly developing control schedules to adapt for potential bistable flow field development during the landing run. The study addresses another part of the puzzle in exploring the feasibility of reverse thrust capable VPF engines for future sustainable aircraft to reach aviation climate neutrality.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace Engineering; Energy; 4004 Chemical engineering